Brazilian plants with anticholinesterase action – a review (Research, Society and Development, 2022)
Brazil has a large flora distributed throughout its territory, containing the greatest genetic diversity in species in the world, many of them used for therapeutic purposes. Plants are the best sources for discovering bioactive compounds against diseases. Alzheimer's Disease is a neurodegenerative disease characterized by memory loss, mainly affecting the population over 65 years of age. This work describes a survey of extracts and oils obtained from plants of the Brazilian flora with potential anticholinesterase action. A systematic literature review of scientific production in databases from CAPES, Google Scholar, PubMed, Scielo, Science Direct, SciFinder, Scopus and Web of Science was carried out. 41 articles published between 2011 and 2021 were selected. 152 plant species were identified, distributed in 49 botanical families, where the Fabaceae was the most cited with 32 species (21.05%). Extract production was the main form chosen, 253 times (93.36%). The leaves were the most used parts, 94 times (43.12%). Ethanol extractions stood out 140 times (51.66%). Most assays evaluated acetylcholinesterase inhibition in 96-well microplate, 182 assays (54.17%). Of all reported species, 110 promoted inhibitions, of which 66.36% had a high intensity. The study achieved its objective by showing relevant results in the inhibition of AChE, however it is worth mentioning that given the size of our flora, few species were investigated, nor were they tested in vivo to corroborate the results of the in vitro assays.